Hyper Attention and the Rise of the Antinarrative:: Reconsidering the Future of Narrativity - Rose, Ellen (Narrative Works)

(untitled) (The University of New Brunswick, 2012)
An unchallenged certainty often expressed in narratology discourse is that narrative, as a defining aspect of humanity, will remain fundamentally untouched by the emergence of new technologies. This essay challenges that assumption by considering the consequences for narrativity of the increasingly prevalent phenomenon of hyper attention, which appears to be related to online computer use. Specifically, this paper suggests that the emergent cognitive style of hyper attention is linked to both a declining ability and willingness to engage with traditional narrative structures and the rise of the antinarrative, a nonform that eschews such conventions as plot, character development, and resolution.